Peran Zikir dalam Membentuk Kesehatan Mental Jamaah: Studi Kasus Jemaah Surau Asraful Amin Kecamatan Stabat - Syarifuddin Syarifuddin (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
This study aims to look at the role of remembrance in shaping mental health in the congregation of Surau Asraful Amin in Stabat District, Langkat Regency. Recitation in a psychological view has a great spiritual effect, namely as an addition to a sense of faith, devotion, honesty, fortitude and maturity in life. This study used qualitative research methods. Data collection was carried out using the library research method. This method is used to conduct a study of some literature, either in the form of books, magazines, bulletins, newspapers, the internet, seminar results and other sources related to the formulated problem. The results of the study showed: (1) the practice of remembrance at Surau Asraful Amin, Stabat District, succeeded in changing the behavior of worshipers at this mosque for the better; (2) the practice of remembrance carried out at Surau Asraful Amin in shaping the mental health of the congregation has succeeded in bringing the congregation to happiness and mental health and even being able to develop their potential optimally.